Adaptive Sliding-Mode Synchronization of the Memristor-Based Sixth-Order Uncertain Chaotic System and Its Application in Image Encryption - Yao, Xiurong; Chen, Xiangyong; Liu, Huawei; Sun, Li; He, Liping (Frontiers in Physics, 2022)
This paper presents a memristor-based sixth-order chaotic circuit which is designed based on Chua’s circuit by flux-controlled memristor and charge-controlled memristor. The chaotic characteristics of the chaotic system are analyzed and the chaotic phase diagrams are drawn. The specific upper bound information of the model uncertainty and external disturbance is unknown. We design an adaptive terminal sliding mode control law for such chaotic systems, which not only compensates the influence of the uncertainty and disturbance, but also the synchronization error system is the fixed-time stable when the sliding motion takes place. And the accessibility of the sliding surface is guaranteed. Thus, the sufficient conditions for the synchronization of the considered systems are derived. Simulation examples show the effectiveness and superiority of the control scheme. The synchronization strategy is applied to image encryption, and the results show that the encryption effect is excellent and has strong anti-disturbance ability.